MODEL DASAR KONSEP PASAR DALAM PERSPEKTIF EKONOMI ISLAM - Suprihatin Suprihatin (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2017)
The root cause of the difference in economics is the difference of the viewpoint (insight) in seeing the world. The viewpoint of empiricism makes the source of knowledge only to experience and reason alone, so in axiology the value of the benefit it develops is based only on physical sensitivity. The point of view of idealism, departing from the developed postulates of reason and revelation. Axiologically, this science is developed to respond to physical happiness maupn non physical, worldly and ukhrowi. But in the standpoint of idealism there is still a difference of viewpoints in seeing the world. Some can still dialogue with the value of empiricism, others reject the value of empiricism. This paper illustrates that the source of economic science consists of empiricism, reason and revelation that produce a market concept that considers the human needs physically and spiritually comprehensively within the scope of microeconomics.